METHODS FOR RESEARCH TECHNOLOGY FOR PRODUCTION OF CANNED SECOND COURSES FROM RAW MATERIALS OF GRAPE LEAVES - Atakulova, Dilfuza (Innovatsion texnologiyalar, 2024)
In this article, a complete analysis of grape leaves reveals their unique composition, and the presence of tartaric, citric, succinic and oxalic acids in grape leaves is determined by reversephase high-performance liquid chromatography (HPLC). The composition and amount of organic matter in grape leaves have been studied using tartaric acid, citric acid, succinic acid and oxalic acid as an example; their amount in selected varieties of Russia ranges from 0.93-2.35 m-equiv g/100 g, and in Uzbekistan fluctuate between 0.5-5.56 m-eq g/100 g